Latin America in the world economy : recent development and trends - Carranza, Jorge Espinosa; Rodriguez, Louis A.; Lord, Montague J.; Inter-American Development Bank. (Washington, D.C. : Inter-American Development Bank, Economic and Social Development Dept., 1975)
The text discussed trends in the international economy as well as market structure and trends of Latin America's primary commodity exports.
Includes bibliographic references
kjo 18/01/2019
Loans
Keywords: International economic relations; Latin America